Selenoprotein P Is the Major Selenium Transport Protein in Mouse Milk - Hill, Kristina E.; Motley, Amy K.; Winfrey, Virginia P.; Burk, Raymond F. (PLOS ONE, 2014)
Selenium is transferred from the mouse dam to its neonate via milk. Milk contains selenium in selenoprotein form as selenoprotein P (Sepp1) and glutathione peroxidase-3 (Gpx3) as well as in non-specific protein form as selenomethionine. Selenium is also present in milk in uncharacterized small-molecule form. We eliminated selenomethionine from the mice in these experiments by feeding a diet that contained sodium selenite as the source of selenium. Selenium-replete dams with deletion of Sepp1 or Gpx3 were studied to assess the effects of these genes on selenium transfer to the neonate. Sepp1 knockout caused a drop in milk selenium to 27% of the value in wild-type milk and a drop in selenium acquisition by the neonates to 35%. In addition to decreasing milk selenium by eliminating Sepp1, deletion of Sepp1 causes a decline in whole-body selenium, which likely also contributes to the decreased transfer of selenium to the neonate. Deletion of Gpx3 did not decrease milk selenium content or neonate selenium acquisition by measurable amounts. Thus, when the dam is fed selenium-adequate diet (0.25 mg selenium/kg diet), milk Sepp1 transfers a large amount of selenium to neonates but the transfer of selenium by Gpx3 is below detection by our methods.